Revisión sistemática sobre la relación de la caries dental entre población no vidente - Cortes Martínez, Anderson Alberto; Maníos Quevedo, Angy Vanessa; Troya García, Laura Valentina (Universidad Antonio Nariño, 2022)
Caries is one of the most prevalent oral pathologies in the world, affecting all types of population; however, the blind population may present a greater risk of affecting their quality of life if not intervened in time